2013
DOI: 10.1371/journal.pone.0082362
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Ultra-Conserved Elements in Drosophilids and Vertebrates

Abstract: Metazoan genomes contain many ultra-conserved elements (UCEs), long sequences identical between distant species. In this study we identified UCEs in drosophilid and vertebrate species with a similar level of phylogenetic divergence measured at protein-coding regions, and demonstrated that both the length and number of UCEs are larger in vertebrates. The proportion of non-exonic UCEs declines in distant drosophilids whilst an opposite trend was observed in vertebrates. We generated a set of 2,126 Sophophora UCE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 70 publications
(119 reference statements)
2
25
0
Order By: Relevance
“…It is possible that functional differences between these two types of data may lead to incompatible branch length estimation. All of our Sanger data were protein-coding or ribosomal DNA sequence from nuclear genes, whereas many UCE loci in general do not overlap with protein-coding regions, but rather appear to act as enhancers or splicing regulators [ 48 ]. Methods that jointly estimate divergence ages and tree topology, such as BEAST, have further seldom been employed to date with UCE or other genomic-scale data due to computational constraints.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that functional differences between these two types of data may lead to incompatible branch length estimation. All of our Sanger data were protein-coding or ribosomal DNA sequence from nuclear genes, whereas many UCE loci in general do not overlap with protein-coding regions, but rather appear to act as enhancers or splicing regulators [ 48 ]. Methods that jointly estimate divergence ages and tree topology, such as BEAST, have further seldom been employed to date with UCE or other genomic-scale data due to computational constraints.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, CNEs represent an abundant class of noncoding features under purifying selection that may influence the landscape of TE insertions. Previous work showed that artificially-induced TE insertions are depleted in the most highly conserved CNEs (so-called “ultra-conserved elements”) (Makunin et al , 2013). However the non-random target preferences, requirement for marker gene activation in TE detection, and experimental origin of the TEs analyzed by Makunin et al (2013) do not allow conclusions to be drawn about CNE-based constraints on insertion of the endogenous set of TE families in natural populations.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work showed that artificially-induced TE insertions are depleted in the most highly conserved CNEs (so-called “ultra-conserved elements”) (Makunin et al , 2013). However the non-random target preferences, requirement for marker gene activation in TE detection, and experimental origin of the TEs analyzed by Makunin et al (2013) do not allow conclusions to be drawn about CNE-based constraints on insertion of the endogenous set of TE families in natural populations. Resolving whether CNEs influence the landscape of TE insertion in natural populations of D. melanogaster will provide further insight into the factors governing TE dynamics in this species, and contribute to our broader understanding of the forces that shape genome organization and molecular evolution in general.…”
Section: Introductionmentioning
confidence: 99%
“…Three of these insertions are partially located in UTRs of genes involved in developmental processes (grh, pld, ssdp). There is therefore strong support for proposing that these "conserved noncoding insertions" became domesticated in the common ancestor of the melanogaster group (15)(16)(17)(18)(19)(20) My (24)).…”
Section: Ancient Transposition Eventsmentioning
confidence: 99%
“…The complementarity of these approaches is at the core of many methods for identifying selection, such as the McDonald & Kreitman test (14) or, more recently, the estimation of deleterious fitness effects (DFE) (15)(16)(17). In the fruitfly, Drosophila melanogaster, many characterizations of highly conserved elements have been proposed, based on different sets of species and identity criteria (2,12,18). However, no systematic study of selection in CNEs combining genome-wide interspecific comparisons with analysis of intra-population polymorphism and selection yet exists in melanogaster.…”
Section: Introductionmentioning
confidence: 99%